“My greetings to you, general of the generals in the world of science ...” Letters of rector of Vologda seminary, archpriest Nikolai Malinovsky to N. N. Glubokovsky (1907–1910) - Pavel Shirokov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article makes public letters of a well-known author of the handbook in dogmatic theology, Rector of Vologda Theological Seminary, Archpriest Nikolai Malinovsky. The letters are addressed to the famous theologian, exegete and church historian Nikolai Nikanorovich Glubokovsky. They date back to the time of the pedagogical activity of N. N. Glubokovsky at St. Petersburg Theological Academy, where he worked from 1891 until the time of its closure. Archpriest Nikolai Malinovsky and N. N. Glubokovsky were natives of Vologda Guberniya and were graduates of Vologda Seminary. The author of the letters touched upon various aspects and problems of theological education. The letters of the Rector of the Seminary are a valuable source which reflects the life of Vologda Theological Seminary in one of the most diffi cult periods of its history, overshadowed by the revolutionary turmoil. Many of the materials published here shed light on certain events that took place at the Theological School of Vologda Diocese. Some documents deal with one of the graduates, later teacher, of Vologda Seminary, i. e. Bishop of Saratov and Tsaritsyn Ioann (Kratirov). The purpose of the article is a comprehensive analysis of this epistolary heritage; it is directly related to the history of secondary theological education in Vologda Diocese. These letters discover new facts, evaluate relevant historical events, which cannot always be done by studying historical documents only. The research methodology is based on the historical method, which allows one to assess historical events in Vologda Theological Seminary at the beginning of the twentieth century. The published letters are kept in the archival fund of N.N. Glubokovsky in the Manuscript Department of the Russian National Library and have not been used by researchers before.